Long-term care in orthotopic liver transplantation - Maria C. Morelli; Antonio D. Pinna (Italian Journal of Medicine, 2013)
Orthotopic liver transplantation is the treatment of choice for selected patients with end-stage liver disease or acute liver failure. Given the excellent long-term survival associated with this procedure, increasing emphasis is being placed on the recognition and prevention of post-transplant complications, detection of recurrent liver disease, and effective management of immunosuppressive drug therapy, which involves regular monitoring of blood levels and the identification of adverse effects and drug interactions. In this context, close interaction between the transplant surgeon, the hepatologist, and the family physician is of great value. The purpose of the present article is to review the multidisciplinary, long-term care of liver transplant recipients, the detection and management of the most common post-transplant complications, and the effects of immunosuppression. The article is based on a PubMed search for articles (original research, reviews, meta-analyses) published between 1995 and 2010. The search terms used were ‘‘liver transplantation’’ AND any of the following: cardiovascular complications, long-term complications, malignancy, post-transplant care.